Insufficient evidence for 'shaken baby syndrome' – a systematic review. (1st March 2017) - Lynøe, Niels; Elinder, Göran; Hallberg, Boubou; Rosén, Måns; Sundgren, Pia; Eriksson, Anders
Abstract: Shaken baby syndrome has typically been associated with findings of subdural haematoma, retinal haemorrhages and encephalopathy, which are referred to as the triad. During the last decade, however, the certainty with which the triad can indicate that an infant has been violently shaken has been increasingly questioned. The aim of this study was to determine the diagnostic accuracy of the triad in detecting that an infant had been shaken. The literature search was performed using PubMed, Embase and the Cochrane Library up to October 15, 2015. Relevant publications were assessed for the risk of bias using the QUADAS tool and were classified as having a low, moderate or high risk of bias according to predefined criteria. The reference standards were confessions or witnessed cases of shaking or accidents. The search generated 3773 abstracts, 1064 were assessed as possibly relevant and read as full texts, and 30 studies were ultimately included. Of these, 28 were assessed as having a high risk of bias, which was associated with methodological shortcomings as well as circular reasoning when classifying shaken baby cases and controls. The two studies with a moderate risk of bias used confessions and convictions when classifying shaken baby cases, but their different designs made a meta‐analysis impossible. None of the studies had a low risk of bias. Conclusion: The systematic review indicates that there is insufficient scientific evidence on which to assess the diagnostic accuracy of the triad in identifying traumatic shaking (very low‐quality evidence). It was also demonstrated that there is limited scientific evidence that the triad and therefore its components can be associated with traumatic shaking (low‐quality evidence). Abstract :